The marriage market for immigrant families in Chosǒn Korea after the Imjin War: Women, integration, and cultural capital - Han, Sangwoo (International Journal of Asian Studies, 2021)
Challenging the myth of premodern Korea as ethnically homogenous, this study focuses on immigrant marriages in Chosǒn Korea following Japanese invasions (Imjin War, 1592-1598). By examining household registers and genealogies, I investigate the status of women who married into the families of Japanese and Ming Chinese immigrants and the social consequences of such marriages. The results unexpectedly indicate that immigrant families rarely intermarried, preferring integration with local families. As a means of acquiring social and cultural capital, Korean brides from elite families were vital to the success of immigrant families in forming social networks and in producing candidates for the civil service examinations, with failure to obtain such a bride proving a potential long-Term obstacle to social advancement. There is a noticeable difference between families of Chinese and Japanese origin in this context due to the preference shown by Korean families for the descendants of Ming generals over Japanese defectors. Contributing to a growing number of studies that question whether the Korean family was fully Confucianized in the seventeenth century with a consequent decline in the status of women, this study argues that women possessed social and cultural capital and held particular value for immigrant families.
Keywords: Hideyoshi's invasions of Korea; Imjin War; immigration; Korea; Korean history; marriage market; status of woman